Detecting Fraud in Financial Statements Through the Fraud Triangle Model: The Case of Indonesia - Agoestina Mappadang (Asia Pacific Fraud Journal, 2023)
Referring to ACFE Global’s in the year 2016 until 2018 RTTN, fraudulent financial statement detection is a typical frequency occurrence and gets a large median loss. This study’s purpose is to determine the perspective of the fraud triangle as measured by three elements where fraud occurs in financial statements and is proxied by earnings management. The population is chosen from banking industries that have been listed on the Indonesia Stock Exchange in 2018-2020. The research sample was 25 banks based on the purposive sampling method as criteria sampling. Objects found are 75 objects and hypothesis testing used binary logistic regression. The results show that the fraud triangle perspective simultaneously affects fraud on financial statements. But, partially only pressure factors as proxied by return on assets were shown to be significantly positive, while other pressure factors were financial stability, external pressures, the nature of the industry, effective monitoring with the measure by the independent commissioner, and the rationalization factor, measured by total accruals (TACC) have no significant. The fraud triangle measurement is only used in this research to detect fraud. In addition, very limited sample use because it only covers 4 years so it cannot provide sufficient confidence. It is important to ascertain and analyze fraud factors that can affect financial reporting to minimize fraud that occurs. Management must obtain the widest possible information for making the right decisions so that the triggers of fraud can be minimized and eliminated